2020
DOI: 10.1155/2020/2760979
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract of the Infructescence of Platycarya strobilacea Sieb. et Zucc. Induces Methuosis of Human Nasopharyngeal Carcinoma Cells

Abstract: The infructescence of Platycarya strobilacea Sieb. et Zucc. (PS) has been used in the treatment of rhinitis and sinusitis in clinical practice. Our preliminary study showed that an ethanol extract of the infructescence of PS (EPS) had significant antinasopharyngeal carcinoma (NPC) effects in vitro. However, the mechanism underlying the NPS cell death induced by EPS remains unclear. The aim of the present study was to investigate the inhibitory effects of EPS on NPC cells and to elucidate the underlying mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous studies have revealed that the drug has a high content of polyphenols, ellagitannins, and flavone‐related compounds. These ingredients are responsible for eliminating toxic heat, activating blood circulation, relieving swelling, and ameliorating pain in pharmacological research [30]. But the bioactive compounds that greatly contribute to the pharmacological effect remain unclear due to the complexity and the synergic actions of the constituents of the drug.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that the drug has a high content of polyphenols, ellagitannins, and flavone‐related compounds. These ingredients are responsible for eliminating toxic heat, activating blood circulation, relieving swelling, and ameliorating pain in pharmacological research [30]. But the bioactive compounds that greatly contribute to the pharmacological effect remain unclear due to the complexity and the synergic actions of the constituents of the drug.…”
Section: Resultsmentioning
confidence: 99%
“…(EPS) demonstrated potent antinasopharyngeal cancer properties in vitro . The production of CNE1 and CNE2 cell fusion and vacuoles, the disruption of lysosomal vesicle transit, and the activation of methuosis were all linked to the anticancer effects of EPS ( Liu et al, 2020 ).…”
Section: Anticancer Therapies Targeting Macropinocytosismentioning
confidence: 99%